Eksistensi Mahar dalam Perkawinan Menurut Abu Hanifah: Sebuah Pendekatan Hukum Melalui Kerangka Metodologi Ushul Fiqh - Winarno, Winarno (ASY SYAR'IYYAH: JURNAL ILMU SYARI'AH DAN PERBANKAN ISLAM, 2018)
The validity of a marriage in the Islamic Shari’a must fulfill harmony and the conditions that have been set. Beside that, there ia a provision stipulated by Allah Swt. as the obligation of prospective husbands in the implementation on the marriage contract, namely regarding or dowry or dowry. As explained in the Al-Qur’an letter An-Nisa ‘verse 4. Because the gift of dowry is an obligation on the basis of willingness, the rate of dowry is not determined by the number or amount. Regarding the maximum amount of dowry, the ulama or prist of the school of thought, it was agreed that there was no maximum limit, but they differed in their opinion about the minimum limit.According to Abu Hanifah the defination of marriage is a contract (agreement) exchange of benefits between husbend and wife so that the marriage contract is based on the contract of sale and considers the gift of dowry as a substitute for a woman’s virginity because Abu Hanifah himself is known as an expert in Kuffah city.Conclusions that can be taken in writing this journal, that Abu Hanifah in applying every law is based on the Al-Qur’an, hadits, fatwa of friends, ijma’ and if it is not there then kias, istihsan, and urf.